Impact of Oral Chemotherapy Management Program on Capecitabine Toxicity Management. Issue 7 (July 2021) - Nhean, Salin; Kostoff, Diana; Yang, Jessica J.; Vogel, Vishnuprabha; Rybkin, Igor I.
Abstract : PURPOSE: Increasing use of oral chemotherapy has created unique challenges related to patient safety and compliance. To address this issue, the Henry Ford Cancer Institute at Henry Ford Health System developed and implemented a system-wide, multidisciplinary program named the Oral Chemotherapy Management Program (OCMP). The purpose of this study was to evaluate the impact of OCMP on patient outcomes in those receiving capecitabine. METHODS: This was a retrospective, quasi-experimental study that compared outcomes in patients receiving capecitabine before and after OCMP implementation. The co-primary outcomes were incidence(s) of grade 1-4 and grade 3-4 adverse effects (AEs) associated with capecitabine. Secondary outcomes were emergency department (ED) visits, hospitalizations because of toxicity, and adherence rate. RESULTS: OCMP patients had significantly lower overall incidence of AE of any grade (58.9% v 70.3%; 95% CI, 0.39 to 0.94; P = .03). OCMP implementation significantly lowered incidence of any grade and grade 3-4 nausea, vomiting, and/or diarrhea, and grade 3-4 hand-foot syndrome. It resulted in the decreased number of ED visits (8.9% v 18.9%; P = .005) and hospitalizations (6.3% v 17.1%; P = .002), as well as improved medication adherence rates (0.94 v 0.97; P = .03). CONCLUSION: Most patients who developed capecitabine-related AE required intervention by OCMP. Implementation of OCMP reduced the incidence of high-grade AE, decreased the number of ED visits and hospitalizations because of AE, and improved the medication adherence rate.